Water chemical analysis of the oxbow lakes near the Upper-Tisza River - Babka, Beáta; Szabó, Szilárd (Acta Geographica Debrecina Landscape & Environment series, 2007)
The Tisza river plays an important role in the life of Eastern Hungary. Beside the river there are several oxbow lakes, cut off meanders. In this paper the water quality of these lakes was examined from the section of Tarpa to Rakamaz. 45 oxbow lakes were sampled and the chemical parameters were determined. Sodium was used as a pollutant (sewage water) indicator and 2 lakes were found extremely polluted. The lakes outside the dam were slightly polluted because of the lack of renewal of the water body and the ones in the active floodplain had good quality parameters.